PENGARUH ANTE NATAL CARE (ANC) DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI MASA PANDEMI COVID-19 DI KABUPATEN KARAWANG TAHUN 2021 - Lilis Suryani; Rina Marlina; Maria Alia Rahayu (HSG (Health Science Growth) Journal, 2023)
In Indonesia in 2011, the percentage of pregnant women with anemia with hemoglobin (Hb) levels below 11 g/dl was 30%, and Hb levels below 7 g/dl was 0.5% (1). Based on data from the Karawang District Service, in 2020 there were 8,020 cases of anemic pregnant women. With the COVID-19 pandemic, pregnant women have difficulty getting health services, especially routine checks to determine the condition of pregnancy, checking hemoglobin levels and there is a lack of health education about preventing anemia in pregnancy. So there is a need for an analysis of the condition of pregnant women's hemoglobin levels in the COVID-19 pandemic situation. Therefore, researchers conducted research entitled "The Effect of Ante Natal Care (ANC) on the incidence of anemia in pregnant women during the COVID-19 pandemic". The research design in this study used a descriptive-analytical method with a cross-sectional approach. The population in this study were all pregnant women who had ANC in 8 midwife practice in the Karawang Regency area, totaling 150 pregnant women. The research sample was obtained from 112 pregnant women using accidental sampling techniques, data collection techniques using secondary data or KIA books for pregnant women, and primary by direct interviews and examination of Hb levels. The results of the study showed that 17.0% of pregnant women had anemia, 25.0% of pregnant women had irregular ANC and there was a relationship between ANC (p=0.007) and the incidence of anemia in pregnant women. It is hoped that mothers will routinely carry out pregnancy checks to get enough blood-boosting tablets and pregnant women are expected to comply with taking a minimum of 90 blood-boosting tablets during pregnancy and continue until 40 days of the postpartum period. Midwives and cadres remind pregnant women to carry out pregnancy checks at least 6 times at health services to get Blood Supplement Tablets. Keywords: Pregnant women, Ante Natal Care, Anemia, Karawang